2021
DOI: 10.1504/ijmlo.2021.111596
|View full text |Cite
|
Sign up to set email alerts
|

A mobile game-based learning system with personalised conceptual level and mastery learning approach to promoting students' learning perceptions and achievements

Abstract: Mobile learning game has been widely used for encouraging students whenever and wherever. However, several studies have indicated that without properly incorporating students' personalised characteristic and learning assistance mechanism into the digital game-based learning environment might fail to motivate students learning and to help them acquire knowledge. To address this issue, this study proposes an integrated learning diagnosis and mastery learning mechanism to generate appropriate gaming stage accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…This finding suggests that personalization, interaction and convenience can strengthen users’ perceived value. The results are aligned with the research of Komalawardhana et al ( 2021 ), Qi et al ( 2021 ), Al-Adwan ( 2020 ). Besides, personalization and convenience will augment students’ confirmation about MOOCs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding suggests that personalization, interaction and convenience can strengthen users’ perceived value. The results are aligned with the research of Komalawardhana et al ( 2021 ), Qi et al ( 2021 ), Al-Adwan ( 2020 ). Besides, personalization and convenience will augment students’ confirmation about MOOCs.…”
Section: Discussionsupporting
confidence: 91%
“…It has been well-recognized that personalization is of huge importance for effective MOOCs learning given to the massive volume of a course (Yu et al, 2017 ). Komalawardhana et al ( 2021 ) reported that the personalized conceptual learning is helpful to promote students’ learning achievement. System quality in the e-learning system is positively associated with the confirmation of system (Lin & Wang, 2012 ).…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…In addition, without careful design, digital games may lack proper guidance and support, emphasizing the necessity of incorporating pedagogy into game-based learning (Pivec et al, 2004). In order to achieve effective learning outcomes through digital games, a digital game should be designed based on a strong pedagogical foundation and instructional theories and strategies (Kebritchi, 2008;Komalawardhana et al, 2021;…”
Section: Introductionmentioning
confidence: 99%
“…In addition, without careful design, digital games may lack proper guidance and support, emphasizing the necessity of incorporating pedagogy into game‐based learning (Pivec et al, 2004). In order to achieve effective learning outcomes through digital games, a digital game should be designed based on a strong pedagogical foundation and instructional theories and strategies (Kebritchi, 2008; Komalawardhana et al, 2021; Wu et al, 2012). Among different teaching strategies and elements, feedback is acknowledged as a fundamental educational aspect within a digital game, and studies were conducted to delve into this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the systematic review found that learning outcomes includes the evaluation of performance, knowledge, achievement, or skills development like communication skills, interpersonal skills or motor skills (see studies for instance by El-Maghraby, 2021 ; Komalawardhana et al, 2021 ). Affective elements refers to learners’ perceptions, intentions, preferences, attitudes, values or beliefs (for example, see Hew et al, 2020 ; Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%